Regional integration in East Asia - edited by Satoshi Amako (New York United Nations University, 2013)
Regional Integration in East Asia: Theoretical and Historical Perspectives is the culmination of five years of intensive research on Asian regional integration by Waseda University. It re-examines theoretical approaches to comprehending the actual state of integration in the region and presents the most compelling among them. It also examines the state of regional cooperation in Asia in areas ranging from the economy to energy and the environment, security and education. In addition, the book offers long-term historical perspectives, including especially those of Japan, ASEAN and China, on Asian regional integration. Thus, it sheds light on diverse aspects, levels of analysis and time spans, and offers a comprehensive portrayal of the actual condition of Asia and the state of endeavours to build regional cooperation and institutions. This volume will open a new research frontier in Asian regional integration research.
Includes bibliographical references and index.
Keywords: East Asia--Economic integration